Can mHealth improve access to safe blood for transfusion during obstetric emergency? - Rahman A; Akhter S; Nisha MK; Islam SS; Ashraf F; Rahman M; Begum N; Chowdhury ME; Austin A; Anwar I (Dove Medical Press, 2017)
Aminur Rahman,1,2 Sadika Akhter,1 Monjura Khatun Nisha,3 Syed Shariful Islam,4 Fatema Ashraf,5 Monjur Rahman,1 Nazneen Begum,6 Mahbub Elahi Chowdhury,1 Anne Austin,7 Iqbal Anwar1 1International Centre for Diarrhoeal Disease Research, Bangladesh (icddr,b), Dhaka, Bangladesh; 2College of Public Health Sciences, Chulalongkorn University, Bangkok, Thailand; 3Sydney School of Public Health, Sydney Medical School, The University of Sydney, Sydney, NSW, Australia; 4Department of Public Health and Informatics, Bangabandhu Sheikh Mujib Medical University, 5Department of Gyenaecology and Obstetric, Shaheed Suhrawardi Medical College and Hospital, 6Department of Gyenaecology and Obstetric, Dhaka Medical College and Hospital, Dhaka, Bangladesh; 7JSI Research & Training Institute, Inc., Boston, MA, USA Purpose: Of the 99% maternal deaths that take place in developing countries, one-fourth is due to postpartum hemorrhage (PPH). PPH accounts for one-third of all blood transfusions in Bangladesh where the transfusion process is lengthy as most facilities do not have in-house blood bank facilities. In this context, the location where blood is obtained and the processes of obtaining blood products are not standardized, leading to preventable delays in collecting blood, when it is needed. This study evaluated the effectiveness of an online Blood Information Management Application (BIMA) system for reducing lag time in the blood transfusion process.Patients and methods: The study was conducted in a public medical college hospital in Dhaka, Bangladesh, and in two proximate, licensed blood banks between January 2014 and March 2015, using a before after design. A total of 310 women (143 before and 177 after), who needed emergency blood transfusion during their perinatal period, as determined by a medical professional, were included in the study. A median linear regression model was employed to assess the adjusted effect of BIMA on transfusion time.Results: After the introduction of BIMA, the median duration between the identified need for blood and blood transfusion reduced from 152 to 122 minutes (P<0.05). For PPH specifically, the reduction was from 175 to 113 minutes (P<0.05). After introducing BIMA and after adjusting for criteria such as maternal age, education, parity, duty roster of providers, and reasons for blood transfusion, a 24 minute reduction in the time was observed between the identified need for blood and transfusion (P<0.001).Conclusion: BIMA was effective in reducing delays in blood transfusion for emergency obstetric patients. This pilot study suggests that implementing BIMA is one mechanism that has the potential to streamline blood transfusion systems in Bangladesh. Keywords: blood transfusion, online application, postpartum hemorrhage, mhealth, Bangladesh